Maternal and perinatal outcome of oligohydramnios in term pregnancy in rural tertiary care centre - Kagne, Swati; Chate, Sambhaji (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Disorders of amniotic volume is one of the commonest obstetric problem. Amniotic fluid acts as cushion to the foetus allowing musculoskeletal development and also helps in the differentiation of lungs and gastrointestinal tract. Decreased amniotic fluid, known as oligohydramnios, is known to be associated with adverse perinatal outcome. The objective is to study the maternal and perinatal complications of oligohydramnios in term pregnancy. Methods: The present study was carried out in the Department of Obstetrics at rural tertiary care hospital in Maharashtra from February 2018 through October 2018. women with Oligohyamnios were studied for obstetrical and neonatal complications. Results: The incidence of oligohyamnios was 7.6% in present study. The mean age of the study population was 22.6±3.6 years. Induction of labour was required in 44 (61.11%) patients out of which 23 patients underwent emergency LSCS. Low birth weight (birth weight<2.5kg) was found in 14 (19.44%) babies with 11 babies having intrauterine growth restriction. 5-minute APGAR (appearance, pulse, grimace, activity, respiration) score was <7 in 13.88% babies. 16 babied needed NICU admission out of which 1 neonate died. Conclusions: Detection of oligohydramnios increases obstetrical interventions in term pregnancy.